Optimization of Ultrasound Treatment of Beverage from Mango and Carrot with Added Turmeric Using Response Surface Methodology - Leticia X. Lopez-Martinez; Nill Campos-Gonzalez; Victor M. Zamora-Gasga; Jesús A. Domínguez-Avila; Sunil Pareek; Mónica A. Villegas-Ochoa; Sonia G. Sáyago Ayerdi; Gustavo A. Gonzalez-Aguilar (Polish Journal of Food and Nutrition Sciences)
The effect of ultrasound treatment (UT) on a beverage from mango pulp and carrot juice with added turmeric powder on total soluble phenolic content (TSP), total carotenoid content (TC) and antioxidant capacity (AOC) was evaluated. Response surface methodology (RSM) was applied to obtain the optimal formulation of the beverage. The AOC was assigned as a response variable in addition to TSP and TC. Mathematical modeling showed that the formulation with 35% ( v/v ) of mango pulp, 10% ( v/v ) of carrot juice, and 0.7% ( w/v ) of turmeric powder, yielded the highest values of TSP, TC, and AOC. The beverages were subjected to different ultrasound conditions with varying exposure times (ET), sonication amplitudes (SA), and pulse cycles (PC) to obtain the highest values for response variables. Statistical modeling showed that a UT at 21 min ET, 100% SA, and 0.7 s PC, increased TSP, Trolox equivalent antioxidant capacity (TEAC), and ferric reducing antioxidant power (FRAP) by 15.5%, 45.1%, and 15.9%, respectively. Seven phenolic acids, three curcuminoids, five flavonoids, and a xanthonoid were identified in the beverages. The quantities of 3,4-dihydroxybenzoic acid, gallic acid, chlorogenic acids, (+)-catechin, quercetin, kaempferol, (–)-gallocatechin gallate, and mangiferin were higher in the UT beverage compared to the control, suggesting their release from cell-wall structures as a result of UT.